Presenting a Location-Routing Problem for Multi-vehicle Hazardous Materials Transport, Considering the Cost Dependent to the Amount of Materials Loaded - Mohammad Jamali (International Journal of Supply Chain Management, 2019)
Regarding the significance and role of fuel materials in growth of industries, and considering the point that the transportation of these products is always encountered with risk and has its own dangers, and also given the increasing importance and applicability of combined transport (multimodal) in various industries and the prominent role of this type of transportation in the supply chain, in this research, first a bi-objective mathematical model is presented for location-routing the hazardous materials transport considering the weight of materials loaded. In this model, the objective cost function including transportation costs, construction of multimodal transportation terminal (for movement of the type of transport vehicle), and also the risk of transportation of hazardous materials, are minimized. Then, using precise solving methods and using the NSGA II algorithm, the proposed model is solved. After assessment of solving methods, the best solving method is chosen and the model is solved based on the real information received from the Iran Road Maintenance & Transportation Organization, the Islamic Republic of Iran Railways, the National Iranian Oil Refining and Distribution Company. In this research, the problems were divided into three small, medium and large groups, and for each of the solving methods, the evaluation criteria were calculated. The results of this comparison indicated that the non-dominated optimization algorithm outperforms the exact solving method. Therefore, it was concluded that this algorithm should be used to solve the model of real data. Likewise, to ensure the performance of this algorithm, the sensitivity analysis of the model was conducted and it was indicated that by changing the parameters of the model, this algorithm gives the expected results and thus its structural performance is confirmed. Finally, the proposed model indicated how the amount of the carried load of hazardous materials is related to a location-routing problem.